1997
DOI: 10.2527/1997.753828x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of prepubertal feeding level on milk yield potential of dairy heifers: a review.

Abstract: In replacement heifers, high levels of feeding resulting in high growth rates in the prepubertal period can cause severe reduction of the milk production potential. This has been demonstrated in many experiments; however, there are a number of experiments where this effect is not seen. In many cases, the reason for the lack of effect seems fairly obvious (short treatment periods, high pretreatment growth rates, small growth rate differences between treatment groups, variation of growth rates within treatment g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
105
1
8

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(120 citation statements)
references
References 0 publications
4
105
1
8
Order By: Relevance
“…If we also consider the mild (even significant) change in markers of hepatobiliary damage, we may argue that the main factor that could cause a delay of puberty onset was the delayed attainment of an adequate BW. The puberty onset is generally determined by metabolic and endocrine signals related to the nutritional status of the heifer (Sejrsen and Purup, 1997). Among Fusarium mycotoxins, one of the most active in reproductive endocrinology disruption is ZEA but specific controlled studies on dairy heifers are lacking (Fink-Gremmels and Malekinejad, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…If we also consider the mild (even significant) change in markers of hepatobiliary damage, we may argue that the main factor that could cause a delay of puberty onset was the delayed attainment of an adequate BW. The puberty onset is generally determined by metabolic and endocrine signals related to the nutritional status of the heifer (Sejrsen and Purup, 1997). Among Fusarium mycotoxins, one of the most active in reproductive endocrinology disruption is ZEA but specific controlled studies on dairy heifers are lacking (Fink-Gremmels and Malekinejad, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Onset of puberty usually occurs in dairy heifers at 30% to 40% of their expected mature body weight (BW) (Heinrichs, 1993;Van Amburgh et al, 1998). Age and BW are closely interconnected, that is, the negative effect of early calving can be explained by high BW gain before puberty or a too low BW at first calving (Sejrsen and Purup, 1997). Ferrell (1982) reported that age at puberty was not related to body condition score (BCS) of heifers at 452 days of age.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, regular injections of GH showed a positive impact on such mammary growth. Inadequate mammary development around puberty alters milk yield potential (Sejrsen and Purup, 1997). Although BW gain before puberty through high-energy diets decreases mammary development when evaluated independently of dietary treatment, heifers that grow faster do not have an impaired mammary development (Silva et al, 2002).…”
Section: Genetic Considerationsmentioning
confidence: 99%
“…However, age, BW and frame size are closely interrelated, i.e. the negative effect of early calving can be explained by high BW gain prior to puberty or a too low BW at first calving (Robelin, 1986;Sejrsen and Purup, 1997). From 3 months of age until puberty, mammary gland growth is related to BW, mainly due to an increased deposition of adipose tissue (Troccon, 1996).…”
Section: Genetic Considerationsmentioning
confidence: 99%